Hegemoni Ideologi dalam Cerpen “Surga untuk Lelaki yang Tertipu” Karya Adam Yudhistira (Kajian Hegemoni Gramsci) - Fajrul Falah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The background of this research is there is an indication that the short story was created not just accentuate the beauty aspects of language and narration. However, the language in the meaningful short stories and the author's ideological message through imaginary characters constructed. The purpose of this study is to reveal hegemony and ideology that contains short stories “Surga untuk Lelaki yang Tertipu” by Adam Yudhistira. The research approach used in the realm of sociology of literature, with the study of Gramsci hegemony. The research method used is descriptive qualitative. Research data in the form of language; words, phrases, sentences in the short story related ones are described and interpreted with the Gramsci hegemony approach. The results of the study show the relationship between the teacher's figure and Santo like a patron-client. The teacher has a higher status (superior) and the power to rule Santo (inferior). The ideological hegemony was carried out by the teacher's figure towards Santo went well. Because it has and is bound by the same beliefs. The orientation of the two figures is the same, namely heaven. The ideology instilled by the teacher has a significant influence on the Santo, so he wants to take action that sacrifices the lives of others and himself. The act which was originally believed to be true by Santo, but regretted in the end.